2019
DOI: 10.1016/j.colsurfa.2019.02.059
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring food structure during digestion using small-angle scattering and imaging techniques

Abstract: Various studies have shown that food structure has an impact on digestion kinetics. We focus here on the effects of gastric and intestinal enzymes (in-vitro digestion) on two canola seed storage proteins, napin and cruciferin. To monitor structure effect we conducted experiments on gels of these proteins at different pHs, yielding different structures and elastic modulus. What is new is to get information on the mechanisms at the lowest scales, using imaging and radiation scattering at large facilities: Synchr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The positions of the successive extrema coincide with the ones of the form factor of a 5 nm radius sphere. However, the intensity scattered by a homogeneous sphere would be significantly lower than the one observed and this suggests a hollow structure as observed for other plant-based proteins such as globulin from rapeseed [31] and also soy glycinin [32]. Moreover the low q part of the scattering pattern of the sunflower protein clearly shows two characteristic lengths and suggests a bimodal population.…”
Section: Structure Of the Proteins In Bulkmentioning
confidence: 81%
“…The positions of the successive extrema coincide with the ones of the form factor of a 5 nm radius sphere. However, the intensity scattered by a homogeneous sphere would be significantly lower than the one observed and this suggests a hollow structure as observed for other plant-based proteins such as globulin from rapeseed [31] and also soy glycinin [32]. Moreover the low q part of the scattering pattern of the sunflower protein clearly shows two characteristic lengths and suggests a bimodal population.…”
Section: Structure Of the Proteins In Bulkmentioning
confidence: 81%
“…57 The influence of canola structure, first of the gel structure compared to the solution at the same concentration, then of the gel structure varied by the pH of the preparation (6, 9, and 11), on the digestion kinetics (gastric and intestinal), was first illustrated by differences in digestion rates. 57 Differently on casein gels, Bayrak et al 58,59 focused on the gastric digestion by SANS and ultra SANS, either analyzing sample aliquots taken at different digestion time periods 58 or digested sample in real time using a dedicated flow setup. 59 They showed that the elasticity of the gel network, governed by the size and density of the protein micelles, determined the disintegration behavior and diffusivity of pepsin.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Most works concern the digestion of lipids, more precisely their changes in self-assembly during esterification, lipase, and hydrolysis of triglycerides. For proteins, our group studied the digestion of dairy gels, but mainly that of canola gels . The influence of canola structure, first of the gel structure compared to the solution at the same concentration, then of the gel structure varied by the pH of the preparation (6, 9, and 11), on the digestion kinetics (gastric and intestinal), was first illustrated by differences in digestion rates .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because lipolytic processes occur under physiological conditions involving a water soluble enzyme acting on water insoluble lipid substrates, digestion always occurs at the interfaces and is strongly influenced by pH and other solution conditions (Humphreys et al, 2022). X-ray fluorescence microscopy, X-ray and neutron scattering were applied to study the digestion of protein gels formed from canola seed storage proteins in vitro, which enabled to follow the process on the individual protein and the structure connectivity (Pasquier et al, 2019).…”
mentioning
confidence: 99%